Does local ambient temperature impact children's blood pressure? A Chinese National Survey. Issue 1 (December 2016) - Li, Qin; Guo, Yuming; Wei, Dong-Mei; Song, Yi; Song, Jie-Yun; Ma, Jun; Wang, Hai-Jun
Abstract Background Several studies demonstrated a short-term association between ambient temperature and blood pressure. However, few studies have assessed the long-term effect of ambient temperature on children's blood pressure. The present study aimed to investigate the association between long-term exposure to local ambient temperature and children's blood pressure in China. Methods We analyzed the systolic (SBP) and diastolic blood pressure (DBP) data of 71, 763 children from 2010 Chinese National Survey on Students' Construction and Health (CHNSCH), and local annual average ambient temperature, relative humidity, air pollutants data from China Meteorological Administration and Ministry of Environment Protection of China. We used generalized additive model (GAM) with non-linear function to examine the effects of ambient temperature on children's blood pressure. Results The results showed that decrease of ambient temperature was negatively associated with increase of both SBP and DBP in Chinese children while adjusting for individual characteristics, socioeconomic conditions, air pollutants and relative humidity. The largest alteration of SBP related to the temperature difference was observed from 20.4 to 9.6 °C, with 9.0 mmHg (95 % CI: 8.4, 9.5) increase in SBP, while the largest alteration of DBP was observed from 21.7 to 10.2 °C, with 6.1 mmHg (95 % CI: 5.6, 6.6) increase in DBP. However, when temperature below 9.6 and 10.2 °C, SBP and DBP started to decrease, which might be caused by the use of heating system in the extreme cold areas. Conclusions Public health policy should be improved for protecting children's cardiovascular health from adverse effects of low temperature. Development of heating system in moderate cold area might be a good solution.